2020
DOI: 10.3906/bot-2002-13
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stress tolerance in transformed Ajuga bracteosa Wall. ex Benth. regenerants by upregulated gene expression of metabolic pathways

Abstract: The rol oncogenes of Agrobacterium rhizogenes enhance the production of medicinally important compounds in plants and provide a first barrier against the overproduction of reactive oxygen species during biotic and abiotic stress. This study was designed to evaluate the expression of genes involved in biosynthetic pathways and their impact on metabolic contents and environmental stress tolerance in regenerated Ajuga bracteosa Wall. ex Benth. After successful transformation, real-time quantitative PCR confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
(66 reference statements)
5
4
0
Order By: Relevance
“…Multiple in vivo activities including analgesic, anti-inflammatory, antidepressant, and anticoagulant activity was evaluated using BALB/c mice. In the continuation of our previous study [15], estimation of essential elements of transformed regenerated plants of A. bracteosa by atomic absorption spectrophotometry and HPLC fingerprinting of polyphenol content was performed to support our results.…”
Section: Introductionsupporting
confidence: 70%
“…Multiple in vivo activities including analgesic, anti-inflammatory, antidepressant, and anticoagulant activity was evaluated using BALB/c mice. In the continuation of our previous study [15], estimation of essential elements of transformed regenerated plants of A. bracteosa by atomic absorption spectrophotometry and HPLC fingerprinting of polyphenol content was performed to support our results.…”
Section: Introductionsupporting
confidence: 70%
“…RP-HPLC delineated a marked surge in polyphenols of transformed plants than their untransformed counterparts. These differences support our previous ndings indicating that rolABC genes enhanced the expression of biosynthetic pathway genes in transformed regenerants of A. bracteosa [15]. We found that ABRL3 presented highest expression of β-hydroxy β-methylglutaryl-CoA reductase (HMGR), farnesyl diphosphate synthase (FDS), 4-hydroxy-3-methyl-but-2-enyl pyrophosphate synthase (HDS), and phenylalanine ammonia lyase (PAL) genes owing to signi cant phenolic content and antioxidant activity of this line.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple in vivo activities including analgesic, anti-in ammatory, antidepressant, and anticoagulant activity were evaluated using BALB/c mice. In the continuation of our previous study [15], estimation of essential elements of transformed regenerated plants of A. bracteosa by atomic absorption spectrophotometry and HPLC ngerprinting of polyphenol content was performed to support our results.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Salinity can cause osmotic and ionic imbalance, functional and structural protein damage and membrane injury in plants. However, plants can promote some tolerance mechanism linked with signal transduction, reactive oxygen species (ROS) production, induction of antioxidants, synthesizing of osmoprotectants, controlling ion absorption, and expression of salt responsive genes and transcription factor to cope with salinity (Gupta and Huang, 2014;Mishra and Tanna, 2017;Rubnawaz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%